ANALISIS PENGARUH PENERIMAAN DAERAH, INVESTASI DAN TENAGA KERJA TERHADAP PDRB PROVINSI KALIMANTAN BARAT - B2051132001, NOVAN NUGRAHA PRATAMA (Jurnal Ekonomi Daerah (JEDA), 2016)
This research aimed to analyze the influence of local revenues, investment and labor to the Gross Regional Domestic Product (GRDP) of West Borneo Province during the period 2009-2013 research was motivated by the fact that the the Gross Regional Domestic Product (GRDP) of West Borneo Province is very volatile and the value is far behind compared to other provinces in the island of Borneo in the period of observation that this same. This research using panel data on a time series of 2009-2013 and using regression analysis "Pooled EGLS (Cross-section weights) with software Evieuws 9. The results showed that 1) the local revenues positive and significant impact on the Gross Regional Domestic Product (GRDP) with a regression coefficient of 0,216499. 2) Investment positive and significant impact to the Gross Regional Domestic Product (GRDP) with a regression coefficient of 0,23188. 3) labor significant and negatively to the Gross Regional Domestic Product (GRDP) with a regression coefficient of -0.217812. 4) sub variable pad positive and significant to the Gross Regional Domestic Product (GRDP) with a regression coefficient of 0,079539. 5) sub variables government transfer positive and significant to the GDP with a coefficient regression of 0,135112. 6) sub variables PMA positive and not significant to the GDP with a regression coefficient of 0,010320. 7) sub variables pmdn positive and significant to the Gross Regional Domestic Product (GRDP) with a regression coefficient of 0.058665. The test results of determination (R2) regression model R2 in the regression of 0.996326. This shows that the regression model can account for 99.6326 percent of the issues examined in this study. While the rest of 0.3674 percent affected by variables outside the model. Keywords: PDRB, Local Revenues, Investment, Labor